KEMAMPUAN DAYA HAMBAT EKSTRAK DAUN PEGAGAN (Centella asiatica (L.) Urban) TERHADAP PERTUMBUHAN Escherichia coli ATCC 8739 - Agvadila, Tanzila; Ari Sandhi W, Putu; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
This study aims to determine the inhibition of leaf extract of pegagan (Centellla asiatica (L.) Urban) on the growth of Escherichia coli ATCC 8739 and to know its best contact time which can inhibit the growth of Escheriachia coli ATCC 8739 bacteria. The experimental metode was used in this research with consisting of 4 level in 0 hours, 6 hours, 12 hours and 24 hours. Data of research result presented in table and picture form. The data obtained were analyzed using descriptive analysis. The results showed that pegagan leaf extract contain flavonoids, tannins and saponins. Based on quantitative analysis pegagan leaf extract obtained flavonoids of 0.09% and tannin of 0.10%. Leaf extract of pegagan can inhibit the growth of Escherichia coli ATCC 8739 but less than one log cycle and contact time of pegagan extract with Escherichia coli most precisely is 12 hours with decrease of bacteria equal to 1.3 x 101 and 40.62% of bacteria test.